Breaking taboos and the ideological image of childhood in the contemporary books for children (Granice tolerancji w sztuce i w wychowaniu, 2020)
The author presents the book as a cultural medium, thanks to which the child gains access to knowledge resources and a system of values. Books addressed to children constantly and consistently fits into the image of its time, being an important carrier of ideas and ideology, thus becoming a tool of cognition, and the reading sphere a part of the propagated culture. In the text, the author refers to the discourses of childhood ideology proposed by A. Męczkowska-Christiansen and looks for the exemplification of the above-mentioned visions of childhood in contemporary children’s literature. The considerations focus on the discourse of political and aesthetic potentiality, in which, in line with the liberal approach, the child is granted the full right to be present in the public sphere, expressing his own thoughts, feelings and doubts. At the same time, the author looks for topics that cross borders and previously taboo spaces, and also refer to those that remain unmentioned areas, both in children’s literature and in Polish culture.